Nano fertilizers: A Sustainable Technology for Improving Crop Nutrition and Food Security (SAARC Journal of Agriculture, 2025)
The significant reliance on chemical fertilizers in current agricultural techniques, precise crop nutrient control, and soil fertility will pose significant challenges in the coming decades. The injudicious use of synthetic chemical fertilizer has created environmental and human health challenges over the world. Nano fertilizers have a variety of effects on nutrient uptake, plant growth, and development by providing nutrients in the root zones. The efficiency of plant growth, soil quality, and crop production of cereals and other crops are all significantly improved by nano fertilizers. Additionally, it strengthens defenses and increases resistance to stress. There are several methods for loading nano fertilizers, such as direct manufacturing of nutrient-based nanoparticles, encapsulation in the nanoparticulate, and absorption on nanoparticles. Plant species, growth stage, climate, and the size and stability of nanoparticles are affected the absorption and translocation of nano fertilizers in plant tissues. A rapidly emerging cutting-edge agricultural technology for agricultural advancement is nanoparticles. The primary focus of this review, which is based on very recent research, is on the role and interaction of nano-enabled fertilizers with crops and how nano fertilizers can help more effective and sustainable agriculture in the future.SAARC J. Agric., 23(1): 94-110 (2025)